THE MEDIATING & MODERATING EFFECT OF WORK MOTIVATION IN THE RELATIONSHIP BETWEEN WORK ETHICS AND EMPLOYEE PERFORMANCE - Ari Luthfi, Muhammad; Nur Fu'ad, Eko (Distribusi - Journal of Management and Business, 2025)
This study aims to analyze the effect of work ethics on employee performance and the role of work motivation as a mediator and moderator in the relationship between the two. The population of this study were 170 employees of CV. ABC in the production department. The research sample was determined using the Slovin formula, so that 75 respondents were selected through random sampling technique. Data were collected using a questionnaire using a Likert scale, and data analysis was carried out with the help of SmartPLS 4.0. The results showed that work ethics & work motivation affect employee performance and work motivation is able to mediate & moderate the relationship between work ethics and employee performance. These findings support the Social Exchange theory (Blau, 2017), which explains that the reciprocal relationship between companies & employees can increase employee motivation and performance. This study provides recommendations for CV. ABC management to strengthen work ethics. In addition, companies need to increase employee motivation through rewards, incentives, and recognition to create a productive and harmonious work environment. Theoretically, this study expands the application of Social Exchange theory by revealing the dual role of work motivation as a mediator and moderator in the relationship between work ethics and employee performance, and strengthens empirical evidence of the relevance of work motivation theory in an organizational context.